2017
DOI: 10.1177/1687814017712415
|View full text |Cite
|
Sign up to set email alerts
|

Multi-axis synchronous interpolation feed rate adaptive planning with rotational tool center point function under comprehensive constraints

Abstract: Real-time nonlinear error caused by rotation axis motion in five-axis interpolation can be compensated by rotational tool center point function. It is well known that reduction of the interpolation nonlinear error can be achieved effectively by increasing the interpolation steps, but what the value of the steps' number should be has rarely been mentioned in the existing literature. Taking a five-axis interpolation machine tool with B & C swing axis as an example, the real-time planning and controlling for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…For example, Hang et al [16] verified the effectiveness of the RTCP method through MATLAB simulation to analyze the kinematics of a double-turntable five-axis machine tool. Shi et al [17] implemented real-time interpolation planning for five-axis maximum feed speed based on RTCP algorithm, and the experimental results showed that this method can effectively improve the surface quality of parts. Although the RTCP algorithm can effectively control nonlinear error, its implementation method is very expensive because it involves an advanced NC system.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hang et al [16] verified the effectiveness of the RTCP method through MATLAB simulation to analyze the kinematics of a double-turntable five-axis machine tool. Shi et al [17] implemented real-time interpolation planning for five-axis maximum feed speed based on RTCP algorithm, and the experimental results showed that this method can effectively improve the surface quality of parts. Although the RTCP algorithm can effectively control nonlinear error, its implementation method is very expensive because it involves an advanced NC system.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 16 implemented the five-axis transformation function in a conventional CNC system for five-axis G1 tool path interpolation. Zhou et al [17][18][19][20] proposed an adaptive feedrate interpolation with multi-constraints for five-axis parametric tool path. However, the aforementioned works did not implement or consider the five-axis parametric interpolation command format, five-axis parametric interpolation strategy, five-axis transformation function, and 3D cutter compensation in the same time, thus none of them can be applied to real machining applications.…”
Section: Introductionmentioning
confidence: 99%